SEMANTIC AND FUNCTIONAL PECULIARITIES OF SPEAKING VERBS IN ENGLISH AND UZBEK LANGUAGES (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article looks into the semantic and functional quirks of verb usage in Uzbek and English languages with the goal of identifying both language-specific and universal traits. Speaking verbs are examined from lexical-semantic, grammatical, and pragmatic viewpoints. They express the act of verbal communication. Speaking verb classification, semantic subtleties, and syntactic behavior in various communicative circumstances are the main topics of the study. Comparative investigation demonstrates how linguistic and cultural factors impact how speech acts are conceptualized and categorized in Uzbek and English. Verb collocations, pragmatic indicators, and direct and indirect speech constructs that convey speaker purpose and interpersonal interactions are all given particular consideration. The results advance the field of contrastive linguistics and offer insightful information for intercultural communication, language instruction, and translation studies.